Affect and social media : emotion, mediation, anxiety and contagion - Sampson, Tony D.; Maddison, Stephen, 1970-; Ellis, Darren (Radical cultural studies., 2018)
This book offers a radical and timely cross-subject intervention into critical social media studies, comprised of four distinct but related sections which are interspersed with artistic illustrations, depicting the affectivities that flow through social media.